Teachers’ Code-Switching in Pekanbaru Vocational Schools - Jismulatif Jismulatif; Supriusman Supriusman; Eliwarti Eliwarti (Journal of Educational Sciences, 2026)
The aims of this research are to identify the functions of code-switching and to explain why teachers employ code-switching in English classrooms. This study utilized a qualitative research design to investigate the phenomenon of code-switching in English as a Foreign Language (EFL) classrooms. Code-switching data were collected from three schools through classroom observations and audio recordings. To support the analysis, interviews with teachers were conducted to gain deeper insights into their reasons for using code-switching. The findings show that teachers use code-switching in the classroom to give instructions, provide feedback, build students’ confidence and comfort, and support students’ understanding of new English vocabulary. The functions of code-switching performed by teachers are not limited to pedagogical purposes but also relate to behavior management and interpersonal or affective interactions with students. Teachers also use code-switching as a strategic tool by transferring and integrating two languages to enhance student engagement and communication during the teaching and learning process.